(untitled) (Research, Society and Development, 2021)
Objective: to analyze the care practices for drug users in a CAPS ad on the perspective of abstinence and harm reduction. Method: qualitative research, developed in a health service in the countryside located on the border between Rio Grande do Sul / Brazil and Uruguay. Data were collected from six professionals between April and September 2017 through semi-structured interviews as a source of data collection and content analysis for the systematization of the findings. Results: From the analysis, the information was organized into four thematic categories: Toxicological tests and the purposes of their use; Reception and rapid tests for STIs and toxicological tests; Proven abstinence as a criterion for referral to the UAT; and The Consequences of imposing abstinence in the rehabilitation process. Conclusion: It is necessary to reflect on the care process that includes harm reduction actions, excluding the focus of treatment on abstinence.